h - Cavalcanti, Ana.; Deharbe, David; Gaudel, Marie-Claude.; Woodcock, Jim.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 7th International Colloquium on Theoretical Aspects of Computing, ICTAC 2010 held in Natal, Brazil, in September 2010. The 23 revised full papers presented with 2 invited papers and the abstract of 1 invited talk were carefully reviewed and selected from 68 submissions. The papers address all theoretical aspects and methodological issues of computing and are organized in topical sections on grammars, semantics, modelling, the special track on formal aspects of software testing and grand challenge in verified software, on logics, as well as algorithms and types.
Invited Papers and Abstract -- Invariants and Well-Foundedness in Program Algebra -- A Theory of Software Product Line Refinement -- The TLA?+? Proof System: Building a Heterogeneous Verification Platform -- Grammars -- Subtyping Algorithm of Regular Tree Grammars with Disjoint Production Rules -- Minimal Tree Language Extensions: A Keystone of XML Type Compatibility and Evolution -- Tracking Down the Origins of Ambiguity in Context-Free Grammars -- Semantics -- Prioritized slotted-Circus -- A Denotational Semantical Model for Orc Language -- An Extended cCSP with Stable Failures Semantics -- Preference and Non-deterministic Choice -- Modelling -- Material Flow Abstraction of Manufacturing Systems -- Specification and Verification of a MPI Implementation for a MP-SoC -- Special Track: Formal Aspects of Software Testing and Grand Challenge in Verified Software -- Testing of Abstract Components -- Scalable Distributed Concolic Testing: A Case Study on a Flash Storage Platform -- Analyzing a Formal Specification of Mondex Using Model Checking -- Formal Modelling of Separation Kernel Components -- Mechanized Verification with Sharing -- Industrial-Strength Certified SAT Solving through Verified SAT Proof Checking -- Dynamite 2.0: New Features Based on UnSAT-Core Extraction to Improve Verification of Software Requirements -- Logics -- Complete Calculi for Structured Specifications in Fork Algebra -- Towards Managing Dynamic Reconfiguration of Software Systems in a Categorical Setting -- Characterizing Locality (Encapsulation) with Bisimulation -- Justification Logic and History Based Computation -- Algorithms and Types -- A Class of Greedy Algorithms and Its Relation to Greedoids -- On Arithmetic Computations with Hereditarily Finite Sets, Functions and Types -- A Modality for Safe Resource Sharing and Code Reentrancy.
Keywords: Computer science; Computer Science; Computation by Abstract Devices